Doctors' working conditions, wellbeing and hospital quality of care: A multilevel analysis. (March 2021) - Teoh, Kevin Rui-Han; Hassard, Juliet; Cox, Tom
Highlights: Doctors' work conditions at the individual and hospital level predicts their wellbeing. No clear relationships between work conditions and hospital care outcomes. Doctors' wellbeing did not predict hospital-level care outcomes. Multilevel analysis must recognise lack of power and measurement issues. Lack of support for JD-R model at hospital level due to methodological issues. Abstract: Introduction: Doctors' wellbeing is postulated to mediate the relationship between their working conditions and patient care although few studies have tested this. Even fewer have incorporated a multilevel perspective that considers the antecedents of quality of care at the hospital level. This study draws on the job demands-resource model to test the associations between hospital-level care (mortality, patient safety incidents, patient satisfaction) with hospital-level demands (e.g. emergency admissions) and self-reported doctors' job demands, job resources and wellbeing. Method: Multilevel structural equation models were used to test the proposed associations using secondary data involving 13, 239 doctors from 139 acute hospitals in England. Results: Doctors' work engagement was associated with higher levels of job control, better manager support, higher bed occupancy rates, and lower levels of emergency admissions. Presenteeism among doctors was linked with higher work overload and emergency admissions. Doctors' work-related stress was associated with higher levels of work overload. Patient satisfaction with their doctor was associated with doctors' level of work overload and job control, as well as bed occupancy rates. Work overload predicted patient safety incidents, while the number of emergency admission predicted mortality rates. Doctors' wellbeing did not mediate any relationship. Conclusion: Better working conditions for hospital doctors were associated with high levels of work engagement and lower levels of work-related stress and presenteeism, necessitating a focus on their work environment to improve wellbeing. The relationships among doctors' working conditions, wellbeing and patient care were not clear, highlighting the importance of considering both statistical and methodological issues in future research.